THE LINGUOCULTURAL SIGNIFICANCE OF COLOR DESIGNATION IN THE MODERN ENGLISH LANGUAGE - Jumanova Gulhayo Adham qizi; Agzamova D.B (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Color plays a crucial role in visual information, as it is often the first aspect people notice, such as the color of someone’s clothing, skin, or hair. Although there are limited linguistic studies on this topic, insights can be gained through introspection by analyzing how color terms function in various contexts. Numerous scientific studies focus on color, and this article aims to explore the characteristics of the English linguistic worldview through color-related phraseological units. The author concludes that examining these units helps to better understand the distinct national traits of the English and the origins and nuances of their worldview.